Analysis of Science Subject Evaluation Instruments in Elementary Schools based on Stimulus Types and Cognitive Process Dimensions - Fajar Okta Widarta; Ikhsan Ikhsan; Muhammad Dekar; Anggita Rahman (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Students' critical thinking skills in Indonesia are still low, even though these skills are needed in the 21st century. Critical thinking skills must be learned at an early age. One of the ways to teach it is through subject evaluation instruments that are arranged based on higher-order thinking skills. So it is important to know the quality of the evaluation instrument made by the teacher. This study aims to analyze the evaluation instrument made by the teacher based on the type of stimulus and dimensions of cognitive processes. This was quantitative and qualitative descriptive research. Sampling data used the purposive sampling technique. Data was presented in the form of a percentage and then described. A qualitative test was conducted to identify the form of stimulus used in each item. Identifying the dimensions of cognitive processes used sheets based on Bloom's taxonomy. The results of this study indicate that most of the questions do not use a stimulus (> 75%) and are at the level of remembering (> 55%). Based on the results of the analysis, it is concluded that the teacher evaluation instrument is still poor. Training to formulate evaluation instruments for teachers needs to be done.